Pengaruh Kualitas Produk Harga Promosi dan Lokasi Terhadap Keputusan Pembelian Chosik Pada UPT Sikka Inovation Center di Maumere - Nunsio Handrian Meylano; Elisabet Luju; Fatmawati Husen (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research is motivated by the importance of product quality, price, promotion and location on the purchasing decision of Chosik at UPT. Sikka Innovation Center in Maumere. The purpose of this study was to determine the effect of the marketing mix which includes product quality, price, promotion, and location on purchasing decisions. The population in this study is the number of consumers who bought Chosik in the last year which amounted to 244. By using the Slovin formula, the sample in this study was 71 respondents. Data collected through questionnaires and analysis used descriptive statistical methods, namely multiple linear regression. Hypothesis testing through t and F tests. The results of descriptive statistical data analysis showed that respondents' perceptions of the product quality variable (X1) were 75.32 with a good category, the price variable (X2) was 90.0 with a very good category, then the promotion variable ( X3) is 72.34 with a good category while the location variable (X4) is 78.50 with a good category. The F test results show Fcount>Ftable, 9.033>2.51, it can be concluded that 4 variables (X) have a significant effect on purchasing decisions (Y). In addition, the results of the analysis of determination (R2) obtained a coefficient of determination of 0.5952 that the magnitude of the influence of the 4 variables (X) on the purchase decision of Chosik at UPT. Sikka Innovation Center in Maumere by 35.4%.